If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -1(-6)) = 26 Multiply -1 * -6 (2x + 6) = 26 Reorder the terms: (6 + 2x) = 26 Remove parenthesis around (6 + 2x) 6 + 2x = 26 Solving 6 + 2x = 26 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 2x = 26 + -6 Combine like terms: 6 + -6 = 0 0 + 2x = 26 + -6 2x = 26 + -6 Combine like terms: 26 + -6 = 20 2x = 20 Divide each side by '2'. x = 10 Simplifying x = 10
| 55=21x | | Y+3+4x=3y+x | | 90+8x+x=180 | | 12r=4+8r | | 5t+25.5=v | | 12x+-2(4x-6)=28 | | 3.7x-1.6=9.5 | | 14x-13x=7 | | 2(3x+6)=9x+10-3x+2 | | (10x)(5x-17)(7x-1)=180 | | x^3=612 | | X+4-2y=24 | | 180=3x+17+x-9 | | 2x+(x+4)=28 | | 14-3f=-7 | | 100=14-3x | | f(x)=3x^3+7x^2-6x | | 100=6.4b^3 | | 5x-6+3X=3(6X-4)+4 | | 3u^2=-7+6 | | 100=5x+8 | | 9x^2-35x-5=0 | | v=5t+25.5 | | -28+49-2=11+-11x+3 | | 4x+6x+20+x=180 | | 14n-3f=-7 | | 0-4=5y-8 | | 21-9+4x-5x=8x+2x-7 | | 9g+4=31 | | 43=3(x+1)2x | | -11x-12=-56 | | 9(w-2)=36 |